Topiramate for acute affective episodes in bipolar disorder in adults - Pigott, K; Galizia, I; Vasudev, K; Watson, S; Geddes, J; Young, A (John Wiley & Sons, Ltd, 2016)
Bipolar disorder is a common recurrent illness with high levels of chronicity. Previous trials have suggested that the anticonvulsant topiramate may be efficacious in bipolar disorder. This is an update of a previous Cochrane review (last published 2006) on the role of topiramate in bipolar disorder.To assess the effects of topiramate for acute mood episodes in bipolar disorder in adults compared to placebo, alternative pharmacological treatment, and combination pharmacological treatment as measured by treatment of symptoms on specific rating scales for individual episodes.We searched the Cochrane Depression, Anxiety and Neurosis Controlled Trials Register to 13 October 2015, which includes records from the Cochrane Central Register of Controlled Trials (CENTRAL) all years; MEDLINE 1950-; EMBASE 1974-; and PsycINFO 1967-.We performed handsearching, reviewing of grey literature and reference lists, and correspondence with authors and pharmaceutical companies.Randomised controlled trials comparing topiramate with placebo or with active agents in the treatment of acute mood episodes in adult male and female patients with bipolar disorder.Two review authors independently performed data extraction and methodological quality assessment. For analysis, we used odds ratio (OR) for binary efficacy outcomes and mean difference (MD) for continuously distributed outcomes.This review included six studies with a total of 1638 male and female participants, of all ethnic backgrounds in both inpatient and outpatient settings. In five studies, participants were experiencing a manic or mixed episode, and in the other study the participants met the criteria for a depressive phase. Topiramate was compared with placebo and alternative pharmacological treatment as both monotherapy and as adjunctive treatment.Moderate-quality evidence showed topiramate to be no more or less efficacious than placebo as monotherapy, in terms of mean change on Young Mania Rating Scale (YMRS) (range 0 to 60), at endpoint 3 weeks (MD 1.17, 95% confidence interval (CI) -0.52 to 2.86; participants = 664; studies = 3; P = 0.17) and at endpoint 12 weeks (MD -0.58, 95% CI -3.45 to 2.29; participants = 212; studies = 1; P = 0.69; low-quality evidence). For the same outcome, low-quality evidence also showed topiramate to be no more or less efficacious than placebo as add-on therapy (endpoint 12 weeks) (MD -0.14, 95% CI -2.10 to 1.82; participants = 287; studies = 1; P = 0.89) in the treatment of manic and mixed episodes. We found high-quality evidence that lithium was more efficacious than topiramate as monotherapy in the treatment of manic and mixed episodes in terms of mean change on YMRS (range 0 to 60) (endpoint 12 weeks) (MD 8.46, 95% CI 5.86 to 11.06; participants = 449; studies = 2; P < 0.00001).For troublesome side effects experienced of any nature, we found no difference between topiramate and placebo as monotherapy (endpoint 12 weeks) (OR 0.68, 95% CI 0.33 to 1.40; participants = 212; studies = 1; P = 0.30; low-quality evidence) or as add-on therapy (endpoint 12 weeks) (OR 1.10, 95% CI 0.58 to 2.10; participants = 287; studies = 1; P = 0.76; low-quality evidence). In terms of participants experiencing side effects of any nature, we found no difference between topiramate and an alternative drug as monotherapy (endpoint 12 weeks) (OR 0.87, 95% CI 0.50 to 1.52; participants = 230; studies = 1; P = 0.63; low-quality evidence) or as add-on therapy (endpoint 8 weeks) (OR 1.57, 95% CI 0.42 to 5.90; participants = 36; studies = 1; P = 0.50; very low-quality evidence).We considered five of the studies to be at low risk of selection bias for random sequence generation, performance, detection, attrition, and reporting biases, and at unclear risk for allocation concealment and other potential sources of bias. We considered the McIntyre 2000 study to be at high risk of performance bias; unclear risk of bias for random sequence generation, allocation concealment, blinding of outcome assessment, and other potential sources of bias; and at low risk for attrition bias and reporting bias.It is not possible to draw any firm conclusions about the use of topiramate in clinical practice from this evidence. The only high-quality evidence found was that lithium is more efficacious than topiramate when used as monotherapy in the treatment of acute affective episodes in bipolar disorder, and we note that this evidence came from only two studies. Moderate-quality evidence showed that topiramate was no more or less efficacious than placebo as monotherapy when a 3-week endpoint was used, but the quality of the evidence for this outcome at a 12-week endpoint dropped to low. As we graded the quality of the evidence for the other findings as low and very low, it was not possible to draw any conclusions from the results.To best address this research question, if investigators see the indication in so doing, more double-blind randomised controlled trials could be conducted that are more explicit with regard to methodological issues. In particular, investigators could compare placebo, alternative, and combination treatments (including a wide range of mood stabilisers), atypical antipsychotics for manic and mixed episodes, and antidepressants in combination with mood stabilisers or atypical antipsychotics for depressive episodes.